2019
DOI: 10.3390/fermentation5010011
|View full text |Cite
|
Sign up to set email alerts
|

Improved Raoultella planticola Strains for the Production of 2,3-Butanediol from Glycerol

Abstract: Raw glycerol is an industrial byproduct from biodiesel production and is one of the most promising substrates for 2,3-butanediol (2,3-BD) production; however, 2,3-BD is not yet produced by fermentation from glycerol on a commercial scale due to poor process economics. Class 1 microorganism collections were screened and Raoultella planticola strain CECT 843 proved to be the best 2,3-BD producer, achieving (23.3 ± 1.4) g 2,3-BD per L and a yield of 36% (g 2,3-BD per g glycerol). To further increase product conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…strain XRM21 to random mutagenesis using EMS which resulted in a highly productive mutant strain accumulating 119.4 g/L in 65 h against 91.2 g/L BDO generated by wild type strain [50]. In another report by Bustamante et al, (2019), two mutant strains were identified after treatment with EMS accumulating 30% more BDO (~31 g/L) than the wild type, with yield approximating the theoretical maximum [51].…”
Section: Discussionmentioning
confidence: 99%
“…strain XRM21 to random mutagenesis using EMS which resulted in a highly productive mutant strain accumulating 119.4 g/L in 65 h against 91.2 g/L BDO generated by wild type strain [50]. In another report by Bustamante et al, (2019), two mutant strains were identified after treatment with EMS accumulating 30% more BDO (~31 g/L) than the wild type, with yield approximating the theoretical maximum [51].…”
Section: Discussionmentioning
confidence: 99%
“…Another commercial product (1,3‐butadiene) is used extensively in rubber production and can be obtained by the dehydration of bio‐derived 2,3‐BDO 8,9 . Several other applications of 1,3‐butadiene include as a solvent for resins and lacquers, antifreeze agent, octane booster analytical reagent, as well as in cosmetics, perfumery, 10 printing inks, 11 as a plasticizer, 12 and in the synthesis of various pharmaceutical derivatives 13‐16 . Thus, the bio‐based production of 2,3‐BDO can eventually become a sustainable route for all these industrial commodities 17,18 …”
Section: Introductionmentioning
confidence: 99%
“…Bioglycerol, an inevitable by‐product of biodiesel production, could be the most suitable feedstock for 2,3‐BDO synthesis 14,19,20 . The commercialization of several biodiesel plants worldwide has resulted in the availability of huge quantities of bioglycerol at the very low price of 3.5–10 cents lb −1 , which has created the serious problem of its proper disposal/utilization 21 .…”
Section: Introductionmentioning
confidence: 99%
“…LIST OF PUBLICATIONS Bustamante, D., Segarra, S., Montesinos, A., Tortajada, M., Ramón, D., Rojas, A. (2019) Improved Raoultella planticola strains for the production of 2,3-butanediol from glycerol.…”
Section: Experimental Work and Resultsmentioning
confidence: 99%